The Maxim of Truth in Political Interviews - Simonyan, Armine (Armenian Folia Anglistika, 2006)
Language and politics have always been closely interconnected and this correlation has served an ample ground to reveal not only the essence of politics but also the systemic nature of the manifestations of the language units applied in that sphere. The study of the language of a politician on the basis of the theory of speech acts makes it possible to reveal the difference thought and its linguistic expression. The maxim of truth is revealed in political interviews as a combination of the expression of real, individual and social truth.